Variation and change in the encoding of motion events - Goschler, Juliana, 1977-; Stefanowitsch, Anatol, 1970- (Amsterdam ; Philadelphia : John Benjamins Publishing Company, 2013)
English is classified as a satellite-framed language with manner-conflating verbs, but it also has a substantial number of (usually Romance) pathconflating verbs that are used transitively with a locative direct object. In this chapter, I address two aspects of these verbs. Using the case of enter, I show how they are initially used in the satellite-framed English motion construction, leading to a double encoding of the path, and are then integrated into the transitive pattern in order to avoid semantic conflicts within the motion construction. I also show how the use of enter in the motion co.
Introduction -- Variation. Beyond typology : the encoding of motion events across time and varieties / Juliana Goschler and Anatol Stefanowitsch -- Variation -- Typology as a continuum : intratypological evidence from English and Serbo-Croatian / Luna Filipovic -- Same family, different paths : intratypological differences in three Romance languages / Alberto Hijazo-Gascón and Iraide Ibarretxe-Antunano -- Disentangling manner and path : evidence from varieties of German and Romance / Raphael Berthele -- The encoding of motion events : building typology bottom-up from text data in many languages / Bernhard Wälchli and Arnd Sölling -- Motion events in Turkish-German contact varieties / Juliana Goschler -- Variation in the categorization of motion events by Danish, German, Turkish, and L2 Danish speakers / Moiken Jessen and Teresa Cadierno -- Change. Describing motion events in Old and Modern French : discourse effects of a typological change / Anetta Kopecka -- Lexical splits in the encoding of motion events from Archaic to Classical Greek / Tatiana Nikitina -- Caused-motion verbs in the Middle English intransitive motion construction / Judith Huber -- Variation and change in English path verbs and constructions : usage patterns and conceptual structure / Anatol Stefanowitsch.
Includes bibliographical references and index.
Print version record.
Keywords: Motion in language; Language and languages -- Variation; Linguistic change; LANGUAGE ARTS & DISCIPLINES -- Linguistics -- General; Language and languages -- Variation; Linguistic change; Motion in language; Electronic books; Electronic books